In the Name of Justice : Striving for the Rule of Law in China - He, Weifang (Book collections on Project MUSE., 2012)
Of all the issues presented by China's ongoing economic and sociopolitical transformation, none may ultimately prove as consequential as the development of the Chinese legal system. Even as public demand for the rule of law grows, the Chinese Communist Party still interferes in legal affairs and continues in its harsh treatment of human rights lawyers and activists. Both the frequent occurrences of social unrest in recent years and the growing tension between China's various interest groups underline the urgency of developing a sound and sustainable legal system. As one of China's mos.